E-Pasar Application to Improve Economic Stability of MSME in Jombang - Nur Khafidhoh; Azmi Maghfirotul Mutiara Ramadhanty (NEWTON: Networking and Information Technology, 2022)
This e-pasar application can make it easier for MSME actors to promote their products and make it easier for consumers to get information about the products owned by the seller. In this pandemic era, it is very impossible to hold a bazaar so the market cannot operate as usual. The purpose of making this e-pasar application is so that the market can continue to operate as usual and also facilitate buying and selling in this pandemic era. The research method used in making this e-pasar application is the waterfall method. The waterfall method provides a sequential software lifeflow approach starting from the analysis, design, coding, testing, and support stages. This research produces an online market website. This online market website serves to provide convenience to customers so that they can find information about products or goods sold in the market quickly.